Introduction to the special issue on socio-cultural role of technology in digital musical instruments. Issue 2 (15th March 2021) - Tahiroğlu, Koray; Magnusson, Thor
ABSTRACT: This special issue, arising from a symposium in Helsinki in 2019, presents contributions from a diverse group of practitioners, representing a broad range of approaches in the making, thinking and writing about digital musical instruments. The authors consider the socio-cultural role of technology in current and emerging digital music practices with changing social roles, historical and critical reflections. This introduction explains the context and motivation for the issue and summarises the contribution of each of the eight articles. Together they provide what we believe is a unique contribution to the research of new interfaces for musical expression and related areas.